2016
DOI: 10.1038/ngeo2623
|View full text |Cite|
|
Sign up to set email alerts
|

Himalayan megathrust geometry and relation to topography revealed by the Gorkha earthquake

Abstract: Optical Offsets 7To determine the co-seismic horizontal displacement field due to the Gorkha earthquake, we use optical 8 image correlation to measure the displacement of pixels between pre-and post-earthquake satellite im-9 ages. We are able to resolve sub-pixel displacements of less than 1/15th of the Landsat8 pixel resolu-10 tion (i.e. < 1 m) using the COSI-Corr software package images, which helps to increase the signal-to-noise ratio, (4) the deformation field is resolved perpendicular to 16 the look angl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
373
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 345 publications
(430 citation statements)
references
References 44 publications
29
373
1
Order By: Relevance
“…This is also consistent with Evangelidis & Kao (2013) who imaged a high-frequency (HF) source at this depth and location which they relate to rupture termination or geometric complexity. A similar trend was observed in the location of the HF seismic radiation sources in the 2015 Gorkha Earthquake, Nepal (Avouac et al 2015); Elliott et al (2016) show that the HF sources are co-located with a change in dip of the fault plane, though in that case, they were in the middle of the rupture zone.…”
Section: Fault Geometrysupporting
confidence: 49%
See 1 more Smart Citation
“…This is also consistent with Evangelidis & Kao (2013) who imaged a high-frequency (HF) source at this depth and location which they relate to rupture termination or geometric complexity. A similar trend was observed in the location of the HF seismic radiation sources in the 2015 Gorkha Earthquake, Nepal (Avouac et al 2015); Elliott et al (2016) show that the HF sources are co-located with a change in dip of the fault plane, though in that case, they were in the middle of the rupture zone.…”
Section: Fault Geometrysupporting
confidence: 49%
“…Lithological layers such as salt and shale detachment horizons act to compartmentalize slip in narrow depth extents (Nissen et al 2010;Elliott et al 2015a), and the intersection of faults at depth has been suggested as a possible (albeit potentially temporary) barrier to rupture propagation (Elliott et al 2011(Elliott et al , 2016. There has been much discussion on the effect of alongstrike segmentation on the length of ruptures in strike-slip earthquakes (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…9). This has been conjectured to be either structurally controlled by the steeply dipping shallower ramp on the MHT (Elliott et al 2016) or by the lower level of stresses updip of the ruptured zone. Finally, the last stage splitting of the rupture front possibly indicates a stronger patch on the MHT leading to transfer of motion onto a different fault, which has been illuminated through the multiple subevent source modelling.…”
Section: Discussionmentioning
confidence: 99%
“…Rest of the figure caption is same as Fig. 3. in the High Himalaya (Elliott et al 2016) The third major aftershock (M w 5.1) occurred ∼5.5 hr after the previous one and originated close to the southern edge of the mainshock rupture area (Fig. 8).…”
Section: April 25 Aftershocksmentioning
confidence: 99%
See 1 more Smart Citation